Practical Aspects of Recruitment and Retention in Clinical Trials of Rare Genetic Diseases: The Phenylketonuria (PKU) Experience. Issue 1 (8th September 2013) - DeWard, Stephanie J.; Wilson, Ashley; Bausell, Heather; Volz, Ashley S.; Mooney, Kimberly
Abstract: Bringing treatments for rare genetic diseases to patients requires clinical research. Despite increasing activism from patient support and advocacy groups to increase access to clinical research studies, connecting rare disease patients with the clinical research opportunities that may help them has proven challenging. Chief among these challenges are the low incidence of these diseases resulting in a very small pool of known patients with a particular disease, difficulty of diagnosing rare genetic diseases, logistical issues such as long distances to the nearest treatment center, and substantial disease burden leading to loss of independence. Using clinical studies of phenylketonuria as an example, this paper discusses how, based on the authors' collective experience, partnership among clinicians, patients, study coordinators, genetic counselors, dietitians, industry, patient support groups, and families can help overcome the challenges of recruiting and retaining patients in rare disease clinical trials. We discuss specific methods of collaboration, communication, and education as part of a long‐term effort to build a community committed to advancing the medical care of patients with rare genetic diseases. By talking to patients and families regularly about research initiatives and taking steps to make study participation as easy as possible, rare disease clinic staff can help ensure adequate study enrollment and successful study completion.